The Results of Using Art Activity Sets on Coloring to Support Learning Achievement in Art Subjects of First-Grade Students at Ban Khok Ta School - Binroseh, Nor-ardila; Padungpong, Chaiwat (Journal of Information and Learning [JIL], 2024)
This study aims 1) to develop and evaluate the effectiveness of art activity sets focusing on coloring for Grade 1 students based on the 80/80 criterion and 2) to compare the learning achievement of Grade 1 students before and after using the art activity sets. The sample group consisted of students in Prathom 1/1 at Ban Khok Ta School, Su-ngai Padi District, Narathiwat Province, under the Narathiwat Primary Educational Service Area Office, Area 2, in the second semester of the 2022 academic year. A total of 30 students were selected using cluster random sampling, with the classroom as the unit for random sampling. The study utilized three types of tools: 1) three art activity sets, 2) a lesson plan for implementing the art activity sets, and 3) an academic achievement test in the art subject: painting. The statistical analyses conducted include precision, difficulty value, discriminatory power, percentage, mean, standard deviation, and a dependent t-test for hypothesis testing. Results revealed that: 1) the art activity set for academic achievement in coloring for Grade 1 students achieved an efficiency of 81.67/83.44, surpassing the 80/80 criterion, and 2) there was a significant improvement in the coloring skills of Grade 1 students after using the art activity sets, with academic achievement higher than before use, at a statistical significance level of .01.